2014
DOI: 10.1136/jnnp-2013-307207
|View full text |Cite
|
Sign up to set email alerts
|

Autologous haematopoietic stem cell transplantation for aggressive multiple sclerosis: the Swedish experience

Abstract: HSCT is a very effective treatment of inflammatory active MS and can be performed with a high degree of safety at experienced centres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
156
1
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 153 publications
(183 citation statements)
references
References 18 publications
13
156
1
13
Order By: Relevance
“…A large North American cohort study of 145 patients (123 RRMS and 28 SPMS), who failed standard disease-modifying therapies including natalizumab, found the 4-year relapse-free survival rate with AHCT to be 80% and NEDA rate to be 68% [30]. A Swedish study of 48 patients (34 RRMS) who had aggressive disease and had failed conventional treatment, including natalizumab, found the relapse-free survival rate to be 87% and a NEDA rate of 68% also [29]. The high NEDA rates seen in patients treated with AHCT is even more impressive when we consider that such patients generally have more active disease than those patients treated in trials for the other types of DMTs [37].…”
Section: Natalizumabmentioning
confidence: 99%
See 4 more Smart Citations
“…A large North American cohort study of 145 patients (123 RRMS and 28 SPMS), who failed standard disease-modifying therapies including natalizumab, found the 4-year relapse-free survival rate with AHCT to be 80% and NEDA rate to be 68% [30]. A Swedish study of 48 patients (34 RRMS) who had aggressive disease and had failed conventional treatment, including natalizumab, found the relapse-free survival rate to be 87% and a NEDA rate of 68% also [29]. The high NEDA rates seen in patients treated with AHCT is even more impressive when we consider that such patients generally have more active disease than those patients treated in trials for the other types of DMTs [37].…”
Section: Natalizumabmentioning
confidence: 99%
“…Limited data about fertility post-AHCT are available. A cohort study of 48 patients (26 females) with MS reported a total of 8 pregnancies after treatment [29]. A total of five healthy infants were born whereas two pregnancies ended in miscarriage and one was ectopic.…”
Section: Early and Late Complications Of Ahct For Msmentioning
confidence: 99%
See 3 more Smart Citations